Acceptability of community-based mentor mothers to support HIV-positive pregnant women on antiretroviral treatment in western Kenya: a qualitative study - Iris Wanga; Anna Helova; Lisa L. Abuogi; Elizabeth A. Bukusi; Wafula Nalwa; Eliud Akama; Thomas A. Odeny; Janet M. Turan; Maricianah Onono (BMC, 2019)
Abstract Background Option B+ is a comprehensive antiretroviral treatment (ART) designed for HIV-infected pregnant/ postpartum women. However, barriers to implementing Option B+ and establishing long-term ART adherence while facilitating retention in prevention of mother to child transmission of HIV (PMTCT) services remain. Community-based mentor mothers (cMMs) who can provide home-based support for PMTCT services may address some of the barriers to successful adoption and retention in Option B+. Thus, we evaluated the acceptability of using cMMs as home-based support for PMTCT services. Methods Gender-matched in-depth interviews were conducted between September-November 2014 for HIV-infected pregnant/postpartum women and their male partners living in southwestern Kenya (n = 40); additionally, we conducted four focus groups involving 30 health workers (n = 70) within four health facilities. Audio-recordings were transcribed, translated, and then coded using a thematic analytical approach in which data were deductively and inductively coded with support from prior literature, identified themes within the interview guides, and emerging themes from the transcripts utilizing Dedoose software. Results Overall, the study results suggest high acceptability of cMMs among individual participants and health workers. Stigma reduction, improvement of utilization of health care services, as well as ART adherence were most frequently discussed potential benefits of cMMs. Participants pictured a cMM as someone acting as a role model and confidant, and who was over 30 years old. Many respondents raised concerns about breaches of confidentiality and inadvertent disclosure. Respondent suggestions to overcome these issues included the cMM working in different communities than where she lives and attending home-visits with no identifying clothing as an HIV-related health worker. Conclusions The home-based cMM approach may be a beneficial and acceptable strategy for promoting ART adherence and retention within PMTCT services for pregnant/postpartum women living with HIV. Considering the risks of inadvertent disclosure of HIV-infected status and related negative consequences for pregnant/postpartum women living with HIV, similar cMM program designs may benefit from recognizing and addressing these risks. Trial registration The MOTIVATE! study was registered on July 7, 2015 at the ClinicalTrials.gov (NCT02491177).